Oxidative stress and epigenetics in ocular vascular aging: an updated review - Bowen Zhao; Lijia Zhu; Meng Ye; Xiaotong Lou; Qianxue Mou; Yuanyuan Hu; Hong Zhang; Yin Zhao (BMC, 2023)
Abstract Vascular aging is an inevitable process with advancing age, which plays a crucial role in the pathogenesis of cardiovascular and microvascular diseases. Diabetic retinopathy (DR) and age-related macular degeneration (AMD), characterized by microvascular dysfunction, are the common causes of irreversible blindness worldwide, however there is still a lack of effective therapeutic strategies for rescuing the visual function. In order to develop novel treatments, it is essential to illuminate the pathological mechanisms underlying the vascular aging during DR and AMD progression. In this review, we have summarized the recent discoveries of the effects of oxidative stress and epigenetics on microvascular degeneration, which could provide potential therapeutic targets for DR and AMD.